PENURUNAN KADAR EMISI GAS BUANG KARBON MONOKSIDA (CO) DENGAN PENAMBAHAN ARANG AKTIF PADA KENDARAAN BERMOTOR DI YOGYAKARTA - Maryanto, Dicky; Mulasari, Surahma Asti; Suryani, Dyah (Universitas Ahmad Dahlan, 2009)
Background: Growth of motor vehicle in Yogyakarta mean 11,9 percent of year. A new motor vehicle Accretion every year reach 83.761 unit, more than 90 percent among other things vehicle wheel two or motorbike. In line with increase sum up the motor vehicle cause the increase sum up the consumption oil fuel, so that cause the gas throw away the motor vehicle like Carbon Monoxide ( CO), Hydrocarbon ( HC), Oxide Nitrogen ( Nox), Oxide Sulfur (Sox) And partikulat Pb mount also. Excelsior of concentration CO which breathed by human being hence fatal progressively risk accepted by the human being, even cause the death. Nature of not scentless gaseous CO and not chromatic also very the toxic, then CO is often conceived of silent killer. Strive the operation with the modification of burner machine conduct the innovation of muffler. With the addition of glass wool, active charcoal, water or other dissimilar substance having the character of adsorb or absorb. this Research target to Know the degradation of rate of gas emission throw away the carbon monoxide ( CO) with the active charcoal addition a motor vehicle.Â Method: this was experimentant research by one group pre and post design descriptively and analytic. Sample of research some of gas emission throw away the carbon monoxide (CO) high secretory the muffler of motorcycle honda supra, measuring instrument used in this research field observation with the active charcoal addition muffler motorcycle, and measuring instrument of inspection of carbon monoxide rate (CO) By analysis means of Auto Check 974/S. Analysis the data use the one way Anova.Â Result : test of Anova of degradation of rate of gas emission throw away the carbon monoxide ( CO) with the active charcoal addition 50, 100, 150 gram of motor vehicle. Assess the mean difference average the rate 150gr to rate 50gr showing number - 1.17600* meaning active charcoal gift 150gr better the than gift 50gr. Seen from value sig for the line of fifth assess sig 0,035 < 0,05 meaning Ho refused and Ha accepted so that there degradation difference by sig.Â Conclusion : There was degradation of rate of gas emission throw away the carbon monoxide ( CO) with the active charcoal addition at motor vehicle. Keywords : Carbon Monoxide ( CO), Active Charcoal Gift.